2011
DOI: 10.1016/j.ejpain.2010.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Chronic blockade of interleukin‐1 (IL‐1) prevents and attenuates neuropathic pain behavior and spontaneous ectopic neuronal activity following nerve injury

Abstract: Neuropathic pain is a chronic pain state resulting from peripheral nerve injury, characterized by hyperalgesia and allodynia. We have reported that mice with genetic impairment of IL-1 signaling display attenuated neuropathic pain behavior and ectopic neuronal activity. In order to substantiate the role of IL-1 in neuropathic pain, WT mice were implanted subcutaneously with osmotic micropumps containing either IL-1ra or vehicle. Two days following the implantation, two models of neuropathic pain were used; par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
58
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 75 publications
3
58
0
2
Order By: Relevance
“…Activation of Schwann cells in turn promotes their secretion of proinflammatory cytokines, thereby producing a positive feedback mechanism that perpetuates injury 109,110 . Inflammatory cytokines such as IL-1, tumour necrosis factor (TNF) and IL-17 can be produced by many cell types, including Schwann cells, and these factors sensitize Aδ-fibres and C-fibres, triggering neuropathic pain [111][112][113] . Indeed, blocking the TNF signalling pathway with a recombinant human TNF receptorantibody fusion protein has been shown to be beneficial in animal models of diabetic neuro pathy, leading to recovery of nerve conduction velocity and increased expression of myelin basic protein 109 .…”
Section: Box 3 | Satellite Glial Cellsmentioning
confidence: 99%
“…Activation of Schwann cells in turn promotes their secretion of proinflammatory cytokines, thereby producing a positive feedback mechanism that perpetuates injury 109,110 . Inflammatory cytokines such as IL-1, tumour necrosis factor (TNF) and IL-17 can be produced by many cell types, including Schwann cells, and these factors sensitize Aδ-fibres and C-fibres, triggering neuropathic pain [111][112][113] . Indeed, blocking the TNF signalling pathway with a recombinant human TNF receptorantibody fusion protein has been shown to be beneficial in animal models of diabetic neuro pathy, leading to recovery of nerve conduction velocity and increased expression of myelin basic protein 109 .…”
Section: Box 3 | Satellite Glial Cellsmentioning
confidence: 99%
“…Not only are the immune and the nervous systems physically connected-there are resident immune cells in the central nervous system (CNS) and peripheral nerve terminals in immune organs-they also share each other's "languages" for their communication. Thus, cells of the nervous system can use signaling by immune components, such as cytokines and chemokines, to communicate with each other (Steinman 2004;McAllister and van de Water 2009;Ben MenachemZidon et al 2011;Diaz Heijtz et al 2011;Gabay et al 2011;Yirmiya and Goshen 2011), while immune cells possess neurotransmitter receptors and can synthesize neurotransmitter molecules including acetylcholine, glutamate, dopamine, and serotonin (Koval et al 1997;Steinman 2004;Ganea et al 2006;Pocock and Kettenmann 2007;Levite 2008;Kong et al 2010;Patterson 2012).…”
mentioning
confidence: 99%
“…IL-1β is essential for Th17 cell differentiation and maintenance, and Th17 cells are likely the main effector cells that induce epithelial damage (2, 3). Genetic and pharmacologic studies have shown that IL-1β mediates, and IL-1Ra blocks, normal, inflammatory, and neuropathic pain sensations (16)(17)(18)(19).The development of a topical biotherapeutic agent for DED presents a protein engineering challenge, requiring optimization for the biology and topical route of administration. Given the rapid turnover of tear volume (10% min −1 ) (20), blocking the tissue-associated receptor would be preferred over blocking tearassociated ligands, and the agent's target affinity should be maximized to minimize clearance and the frequency of dosing.…”
mentioning
confidence: 99%
“…IL-1β is essential for Th17 cell differentiation and maintenance, and Th17 cells are likely the main effector cells that induce epithelial damage (2, 3). Genetic and pharmacologic studies have shown that IL-1β mediates, and IL-1Ra blocks, normal, inflammatory, and neuropathic pain sensations (16)(17)(18)(19).…”
mentioning
confidence: 99%